Different capacity of in vitro generated myeloid dendritic cells of newborns of healthy and allergic mothers to respond to probiotic strain E. coli O83:K24:H31 - Súkeníková, Lenka; Černý, Viktor; Novotná, Olga; Petrásková, Petra; Boráková, Kristýna; Kolářová, Libuše; Prokešová, Ludmila; Hrdý, Jiří (Immunology letters, 2017)
Allergic diseases belong to one of the most common diseases with steadily increasing incidence even among young children. There is an urgent need to identify a prognostic marker pointing to increased risk of allergy development enabling early preventive measures introduction. It has been shown that administration of selected probiotic strains or mixtures could prevent allergy development. In our study, we have tested the capacity of probiotic strain Escherichia coli O83:K24:H31 (E. coli O83) to promote dendritic cell (DC) maturation and polarisation of immune responses. Increased presence of activation marker CD83 was observed on DC stimulated by E. coli O83 and DC of newborns of allergic mothers have significantly more increased cell surface presence of CD83 in comparison to children of healthy mothers. Increased gene expression and secretion of IL-10 was detected in DC stimulated with E. coli O83 being higher in DC of newborns of healthy mothers in comparison to allergic ones. Generally, increased presence of intracellular cytokines (IL-4, IL-13, IFN-gamma, IL-17A, IL-22, IL-10) was detected in CD4+ T cells cocultured with DC of children of allergic mothers in comparison to healthy ones. E. coli O83 primed DC significantly increased IL-10 and IL-17A in CD4 T cells of newborns of healthy mothers in comparison to the levels detected in CD4 T cells cocultured with control non-stimulated DC. We can conclude E. coli O83 induces dendritic cell maturation and IL-10 production in DC. Newborns of allergic mothers have generally increased reactivity of both DC and CD4 T cells which together with decreased capacity of DC of newborns of allergic mothers to produce IL-10 could support inappropriate immune responses development after allergen encounter.
Keywords: Cord blood; buněčná diferenciace; Mothers; Allergy; Immunity, Maternally-Acquired; Lymphocyte Activation; probiotika; Probiotic; kultivované buňky; CD4-pozitivní T-lymfocyty; Dendritic Cells; Humans; interleukin-17; Interleukins; Probiotics; novorozenec; Female; interleukin-10; Coculture Techniques; interleukin 22; aktivace lymfocytů; Cells, Cultured; ženské pohlaví; CD4-Positive T-Lymphocytes; interleukiny; dendritické buňky; Hypersensitivity; Cell Differentiation; imunita získaná od matky; Adult; alergie; Interleukin-10; Dendritic cell; Interleukin-22; Interleukin-17; dospělí; kokultivační techniky; lidé; matky; Cytokine; Infant, Newborn; Escherichia coli